From Learning to Knowledge: Analysis of Relationships between These Organizational Processes - Lelja Turulja; Nijaz Bajgorić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
Business globalization pressures and rapid technology advances increase the need for firms to continuously change, improve and adapt to changing business environment. Superior business performance is increasingly a function of firm's ability to develop and implement unique and valuable resources, i.e. dynamic capabilities. Among others, literature recognises organisational learning (OL) capability and knowledge management (KM) capability as two very important capabilities for the firms doing business in the knowledge-based economy. Thus, this study draws on dynamic capability view and organisation theory to clarify the nature of the relationships between OL capability and KM capability. The results show that OL capability positively influence KM capability. Furthermore, shared vision as well as openness and experimentation advance the KM capability while dialog and managerial commitment haven't been revealed to significantly influence KM capability. The study provides advances in the field of organisational learning and knowledge management literature by offering empirical analysis that confirm the importance of individual constructs of organisational learning capability for successful knowledge management.
Keywords: D83; 330; knowledge management; organisational learning; information technology; organisation theory; dynamic capabilities